Digital transformation as a sociological challenge is reshaping the roles of university professors - Bahia, Nemeur (The International tax journal, 2025)
In recent years, the higher education sector has witnessed profound technological changes, similar to those occurring across various institutional fields in Algeria. This article aims to shed light on the phenomenon of technostress as a defining feature of the contemporary era, particularly in the context of rapid digital transformations affecting multiple domains, especially higher education. Technostress has become one of the most prominent psychological and professional challenges within the modern university environment. This study is guided by the following central question: How does digital transformation contribute to the emergence of technostress among university professors, and what strategies can be adopted to mitigate its impact? The article begins by clarifying the concept of technostress, its main causes, manifestations, and coping strategies, drawing on a corpus of recent studies. The theoretical insights indicate that technostress arises from a mismatch between the demands of the digital environment and users’ capabilities, and it manifests in various forms. Among its most significant causes are communication overload and the blurring of boundaries between personal and professional life resulting from continuous technological advancements. Conversely, the study identifies a set of preventive mechanisms to limit the spread of this phenomenon.